Problems of Coordination of International Cooperation in Fighting Organized Crime - KOVALSKA, Vita Volodymyrivna (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017, 2017)
The article analyzes the definition of ʽcoordination,ʽ identifies an organizational framework for coordination of international cooperation of entities intended to fight organized crime and specifies their role, as well as suggests the author’s own definition of coordination of international cooperation in fighting organized crime.